Model Blended learning Berbasis Google Classroom Pada Kompetensi Dasar Listrik dan Elektronika (DLE) Terhadap Hasil Belajar - Malahayati Malahayati; Mursyidin Mursyidin; Umrah Hayani; Radhiah Radhiah (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2022)
Government obliged the schools should held the online learning in terms of Covid 19 spreadness. However, the online learning process indicated less effective result. To overcome this problem, a  blended learning model is applied. The blended learning model combines online learning with face-to-face (offline) learning. The purpose of this study was to determine  the response and influence of the blended learning model with google classroom. The method used in this study is an applied research method by using one group pretest posttest design. The study involved students of class X TEI SMKN 1 Simpang Kanan, SIngkil, Aceh. The instrument used wa test questions and questionnaires. Data analyze by looking at the difference in the average score of students at the pretest and posttest result. The data showed that the blended learning model with google classroom had a positive effect on student learning outcomes. It proved from the results of hypothesis testing by using the paired sample test at = 0.05, the sig value is obtained. (2 tailed) of 0.046.It could concluded that Ha is accepted. The data also presented that there were differences in the learning outcomes of class X TEI before and after the implementation. This can be seen from the average score of students at the time of the pretest was 57.11 and the average value of the students at the time of the posttest was 65.88. Meanwhile, the students' response to the blended learning model with the help of Google Classroom is 80.8%. It can be concluded that the Belnded Learning model assisted by Google Classroom is quite effective to be applied to distance learning (online).